Study on the developmental Stages of Spider Mite (Tetranychus urticae Koch) Infesting Country Bean (Journal of Bio-Science, 2009)
The duration of developmental stages of Tetranychus urticae Koch was studied in different months of a year at room temperature. In addition fecundity of this mite was also observed in winter, autumn and summer seasons. T. urticae eggs hatched to larvae in the shortest duration of 1.07 ± 0.26 days and the longest duration of 11.67 ± 2.33 days in April and January, respectively. The larval period of T. urticae took the shortest time of 0.55 ± 0.50 days in May and 2.93 ± 1.07 days in December. The protonymph transformed to deutonymph in 0.89 ± 0.32 day in May and 3.71 ± 1.94 in December and January. The deutonymph required the shortest duration of 0.92 ± 0.41 days in August and the longest of 10.26 ± 1.48 days in January. The temperature played significant (P